Advertisement Remove all ads

X Ex - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

x ex

Advertisement Remove all ads

Solution

\[ \frac{d}{dx}\left( f(x) \right) = \lim_{h \to 0} \frac{f\left( x + h \right) - f\left( x \right)}{h}\]
\[\frac{d}{dx}\left( x e^x \right) = \lim_{h \to 0} \frac{(x + h ) e^{(x + h)} - x e^x}{h}\]
\[ = \lim_{h \to 0} \frac{(x + h) e^x e^h - x e^x}{h}\]
\[ = \lim_{h \to 0} \frac{x e^x e^h + h e^x e^h - x e^x}{h}\]
\[ = \lim_{h \to 0} \frac{x e^x e^h - x e^x}{h} + \lim_{h \to 0} \frac{h e^x e^h}{h}\]
\[ = \lim_{h \to 0} \frac{x e^x \left( e^h - 1 \right)}{h} + \lim_{h \to 0} e^x e^h \]
\[ = x e^x \left( 1 \right) + e^x \left( e^0 \right)\]
\[ = x e^x + e^x\]

Concept: The Concept of Derivative - Algebra of Derivative of Functions
  Is there an error in this question or solution?

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 30 Derivatives
Exercise 30.2 | Q 2.04 | Page 25

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×